1994
DOI: 10.1002/etc.5620130808
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion method for the determination of acid‐volatile sulfides (AVS) in sediment

Abstract: A simplified procedure using diffusion and a sulfide ion selective electrode is described for measuring acid‐volatile sulfides (AVS) in sediment This method yielded at least 10% more AVS than the more common purge‐and trap method The quantity of AVS (based on dry mass of sediment) was found to be dependent on acid concentration and on mass of wet sediment The mean recovery of known additions of sodium sulfide was 93 8 ± 6 7%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…AVS and SEM were determined by combining and optimizing the methods of Hsieh and Yang (1989), Allen et al (1993) and Brouwer and Murphy (1994), within 2 weeks after sample collection (Lasorsa and Casas, 1996). The experimental setup involved a 250 ml three-necked flask in which the reaction was conducted; the flask was sequentially connected to two 250 ml scrubbing bottles, each of which contained 100 ml of 0.5 mol l À1 zinc acetate solution to trap the evolved gases.…”
mentioning
confidence: 99%
“…AVS and SEM were determined by combining and optimizing the methods of Hsieh and Yang (1989), Allen et al (1993) and Brouwer and Murphy (1994), within 2 weeks after sample collection (Lasorsa and Casas, 1996). The experimental setup involved a 250 ml three-necked flask in which the reaction was conducted; the flask was sequentially connected to two 250 ml scrubbing bottles, each of which contained 100 ml of 0.5 mol l À1 zinc acetate solution to trap the evolved gases.…”
mentioning
confidence: 99%
“…Compared with the diffusion method, it is very laborious to use the purge-and-trap method to handle a large number of samples simultaneously: a lot of glassware, gas and space are required (Brouwer and Murphy, 1994). Researchers found that the diffusion method yielded higher AVS concentrations than the purge-and-trap method.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers found that the diffusion method yielded higher AVS concentrations than the purge-and-trap method. They attributed this to the higher efficiency of the diffusion method than the purge-and-trap method and to the prolonged anoxic storage of the samples (Brouwer and Murphy, 1994;Leonard et al, 1996;van Griethuysen et al, 2002). Considering the two points above, a diffusion method modified by van Griethuysen et al (2002) was used for extracting AVS from 3 g wet sediment of each sample in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The AVS method presented by Hsieh and Yang [24] and modified by Brouwer and Murphy [25] and Leonard et al [26] was applied in the present study. The AVS extraction was performed in the anaerobic box to avoid oxidation of sulfide due to exposure to air.…”
Section: Acid Volatile Sulfide (Avs)mentioning
confidence: 99%